Environmental taxes in an economy with distorting taxes and a heterogeneous population - Michael Hoel (University of Oslo, Department of Economics, 2008)
During the last couple of decades, there has been a large literature discussing how the properties of emission taxes are affected by the existence of distortionary taxes. Most of this literature ignores distributional aspects of environmental taxes and other types of environmental policy instruments. The present paper considers a very simple model with heterogeneous households, differing in income earning ability. The tax system i s not necessarily fully optimal. Instead, a tax function is assumed the be exogenously given, but the parameters of this tax function are opmtimally chosen. The rule for the second-best opmtimal environmental tax is derived and compared with the Pigovian rule. The results derived in the present paper are related to the results from the literature on public goods provision under distortionary taxes.
Keywords: H23; H41; Q58; 330; Environmental taxes; public goods; distortionary taxation; Ökosteuer; Öffentliches Gut; Steuerwirkung; Second Best; Theorie